Effectiveness of a Positive Writing Intervention for Chronic Pain: A Randomized Trial. Issue 3 (2nd October 2015) - Ziemer, Kathryn Schaefer; Fuhrmann, Amy; Hoffman, Mary Ann
Abstract: Objectives: There is a need to develop efficient, cost-effective psychological interventions for chronic pain. Expressive writing has been found to produce beneficial psychological and physical outcomes for those with chronic medical conditions. Positive expressive writing may also be beneficial to those with musculoskeletal pain, but this type of writing has not been studied before with this population. The current study was a pilot to explore how chronic pain patients respond to two positive variations of the expressive writing paradigm. Methods: Ninety-three participants with chronic pain were recruited from chronic pain forums and completed the writing exercise. Participants were randomized to either self-compassion or self-efficacy writing and wrote for 20 min once a week for three consecutive weeks. Participants completed baseline and post-writing measures of pain severity, illness intrusiveness, pain acceptance, pain catastrophizing, depression symptoms, life satisfaction, self-compassion and chronic pain self-efficacy. Results: Overall, both types of writing helped participants, who reported that the exercise was a positive experience. Raters were able to accurately identify the writing group for the majority of participants, which indicates that most participants followed the writing instructions. Few differences were found between the two writing groups, though when participants in either group reported an increase in self-compassion or self-efficacy, they also reported better physical and psychological outcomes. Conclusions: Participants with chronic pain appear to be open to self-compassion and self-efficacy writing. Positive writing may be useful to the extent that it increases self-compassion and self-efficacy.